Digital Maturity of Higher Education Institutions in Bosnia and Herzegovina: Teachers' Assessment - Mirela Mabić; Daniela Garbin Praničević (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2021)
This paper presents the research results on digital maturity in higher education institutions in Bosnia and Herzegovina (BiH). Empirical research was conducted among employees of eight public higher education institutions in spring 2020. Digital maturity was examined through seven dimensions. The results show that higher education institutions in BiH started the digitalization process more than five years ago. They have been continuously working on the digitalization of all business processes and activities. According to employees, on a scale from 1 to 5, digitalization of their higher education institutions is somewhere in the middle (between 3 and 4). The institutions have room for improvement in all dimensions.
Keywords: I23; L86; 330; digital maturity; higher education; digitalization